Theoretical and applied mechanics : proceedings of the XVIth International Congress of Theoretical and Applied Mechanics held in Lyngby, Denmark, 19-25 August, 1984 - Niordson, Frithiof I.; Olhoff, Niels (North-Holland ; Sole distributors for the U.S.A. and Canada : Elsevier Science Pub. Co., 1985)
Theoretical and Applied Mechanics covers the proceedings of the 16th International Congress of Theoretical and Applied Mechanics, held at the Technical University of Denmark, Lyngby, Denmark on August 19-25, 1984. The contributors consider the significant advances in the thriving field of mechanics. This book is composed of 21 chapters, and begins with an overview of space research contributions in understanding fluid media mechanics. This topic is followed by discussions on some aspects and fundamentals of mechanics, such as chaos, computer application, resonant phenomena, adiabaticity, and n.